Claspin haploinsufficiency leads to defects in fertility, hyperplasia and an increased oncogenic potential. Issue 19 (14th October 2022) - Madgwick, Suzanne; Luli, Saimir; Sellier, Helene; Butterworth, Jacqueline A.; Leslie, Jack; Moore, Adam J.; Corbin, Emma K.; Yemm, Adrian I.; Chiremba, Robson T.; Tiniakos, Dina; Oakley, Fiona; Perkins, Neil D.; et al.
Abstract : Claspin is an adaptor protein required for ATR-dependent phosphorylation of CHK1 during S-phase following DNA replication stress. Claspin expression is highly variable in cancer, with low levels frequently correlating with poor patient survival. To learn more about the biological consequences of reduced Claspin expression and its effects on tumorigenesis, we investigated mice with a heterozygous knockout of the Clspn gene. Claspin haploinsufficiency resulted in reduced female fertility and a maternally inherited defect in oocyte meiosis I cell cycle progression. Furthermore, aged Clspn +/− mice developed spontaneous lymphoid hyperplasia and increased susceptibility to non-alcoholic fatty liver disease. Importantly, we demonstrate a tumour suppressor role for Claspin. Reduced Claspin levels result in increased liver damage and tumourigenesis in the DEN model of hepatocellular carcinoma. These data reveal that Clspn haploinsufficiency has widespread unanticipated biological effects and establishes the importance of Claspin as a regulatory node controlling tumorigenesis and multiple disease aetiologies.